Visibly acoustic delivery of IR808 into tumor via gas vesicles enhances photothermal therapy efficacy against tumor - Xin Meng; Yanan Feng; Yuanyuan Wang; Chen Lin; Wei Wang; Sutian Zhu; Bing Guo; Huaiyu Wang; Litao Sun; Fei Yan (Ultrasonics Sonochemistry)
Photothermal therapy (PTT) has emerged as a promising new approach in tumor treatment, with the great advantages including non-invasiveness and temporal controllability. However, the effective delivery of photothermal agents into tumor remains a significant challenge, limiting its clinical translational application. In this study, we developed a kind of photothermal agents modified with gas vesicles (GVs), greatly facilitating ultrasound/fluorescence imaging-guided delivery of photothermal agents and enhancing the efficacy of photothermal therapy. The GVs were synthesized and extracted from Halobacterium NRC-1, followed with modification with IR808. The resulting GVs-IR808 were able to be visually tracked by ultrasound and fluorescence imaging. Upon their arrival at the tumor area after systemic administration, ultrasound irradiation was applied to induce the cavitation of GVs-IR808, greatly promoting IR808 delivery into the tumor. The subsequent laser irradiation was applied and resulted in a significant inhibition of tumor growth. In conclusion, our study provides a novel approach for ultrasound/fluorescence dual-modal imaging-guided photothermal treatment of breast tumors.